Treatment of mange in buffaloes with Abamectin - AL-Judi, A.M. H. (The Iraqi Journal of Veterinary Medicine, 2021)
Abamectin activity against mange in buffaloes was evaluated by using 0.2 mg/kg. B. W. of this drug as a single subcutaneous injection for treatment of 50 naturally affected buffaloes with Sarcoptic mange. There were no mites in the skin scraping of treated animals two weeks after treatment , new hair growth appeared in the infected areas four weeks after treatment, along with healing of the skin lesions.